The dissolution of character in late romanticism, 1820-1839 - Cope, Jonas (Edinburgh critical studies in romanticism., 2018)
The Dissolution of Character in Late Romanticism studies texts written by contemporary poets, novelists, essayists, journalists, philosophers, phrenologists, sociologists, gossip-mongers and anonymous correspondents.